The Effectiveness of Acceptance and Commitment-Based Therapy on Perceived Stress, Perception of Illness and Severity of Fatigue in People with Heart Disease - Aghili, Mojtaba; Firozkohi , Mostafa (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Background and Aim: Coronary heart disease is associated with an epidemic and a very high prevalence in both developed and developing countries and is considered as one of the most basic causes of death in people. This research was conducted with the aim of investigating the effectiveness of treatment based on acceptance and commitment on perceived stress, perception of illness and severity of fatigue in people with heart disease. Methods: The research method was a quasi-experimental pre-test-post-test type with a control group. The statistical population of the study included all people with heart disease admitted to Shahid Sayad Shirazi Hospital in Gorgan city in 2022, from among whom 30 people were randomly selected in 2 experimental and control groups (15 people in each group). The experimental group underwent 8 sessions of 60-minute therapy based on acceptance and commitment, and the control group did not receive any intervention until the end of the study. The research tools included the questionnaires of perceived stress by Cohen et al. (1983), perception of illness by Broadbent et al. (2006) and severity of fatigue by Krapp et al. (2001). The research data was analyzed by multivariate analysis of covariance and using spss software version 22. Results: The findings of the research showed that the treatment based on acceptance and commitment is effective on the perceived stress, perception of the disease and severity of fatigue in people with heart disease (P